PENINGKATAN PROTEIN DAN SERAT SERTA UJI ORGANOLEPTIK KERIPIK DENGAN PENAMBAHAN TEPUNG AMPAS TAHU (Glycine Max (L) Merill) - Romdhani, Ahmad Mundzir; Farid, Ulfa Maulida; Uyun, Qurratul; Rahma, Ziyadatur (Program Studi Pendidikan Biologi, 2024)
The aim of study was to determine the content of protein, fiber, and the acceptability of panelists by organoleptic tests on tofu-dregs chips. This research is an experimental study with three comparisons, namely wheat flour with the addition of tofu-dregs flour, namely 100%, 50%:50%, and 25%:75%, with 3 repetitions. This research begins with the manufacture of tofu-dregs flour and then chips are made. The variables tested were protein, fiber and organoleptic tests. Data analysis with one-way ANOVA. The results showed that the addition of tofu dregs flour increased the protein and fiber content in chips. Based on the test results, it was found that the highest protein and fiber content was in the third treatment, namely the comparison of 75% flour: 25% tofu dregs flour with an average protein of 11.39% and 0.91% fiber.